Cool La Nina during the warmth of the Pliocene? - Rickaby, R; Halloran, P (2005)
The role of El Niño-Southern Oscillation (ENSO) in greenhouse warming and climate change remains controversial. During the warmth of the early-mid Pliocene, we find evidence for enhanced thermocline tilt and cold upwelling in the equatorial Pacific, consistent with the prevalence of a La Niña-like state, rather than the proposed persistent warm El Niño-like conditions. Our Pliocene paleothermometer supports the idea of a dynamic "ocean thermostat" in which heating of the tropical Pacific leads to a cooling of the east equatorial Pacific and a La Niña-like state, analogous to observations of a transient increasing east-west sea surface temperature gradient in the 20th-century tropical Pacific.